2005
DOI: 10.1002/mcs.1220080502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flowrate and ionic strength on retention of nonporous micron-sized silica gel particles in gravitational field-flow fractionation

Abstract: Abstract. Retention of nonporous micron-sized silica gel particles in gravitational field-flow fractionation (GFFF) was investigated with respect to the activity of the hydrodynamic lift-forces and surface forces. The hydrodynamic lift-forces act near the channel wall in the same direction as repulsive electrostatic forces against the gravity so that the particles are focused. Although a complete quantitative description of the hydrodynamic lift-forces, which would enable prediction of the retention time, is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Figure 4 shows GrFFF calibration curves obtained with four PS beads (8,12,20, and 40 μm) at a flow rate of 2 mL/min in the different solvents with the channel placed horizontally. In the solvent system A, the slope of the calibration curve (or the sizebased selectivity, S d ) decreases as the viscosity increases.…”
Section: ' Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4 shows GrFFF calibration curves obtained with four PS beads (8,12,20, and 40 μm) at a flow rate of 2 mL/min in the different solvents with the channel placed horizontally. In the solvent system A, the slope of the calibration curve (or the sizebased selectivity, S d ) decreases as the viscosity increases.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…The particles are separated based on their size with larger ones eluting earlier than the smaller ones. GrFFF has been shown to be useful for separation of various types of micrometer-sized particles including coal particles, silica particles, clay particles, starch granules, yeast, and pollens . It has also been shown that GrFFF is sufficiently gentle to allow separation of samples such as lymphocytes, red blood cells, parasites, , stem cells, , and bacteria .…”
mentioning
confidence: 99%
See 2 more Smart Citations